The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5306/wjco.v13.i1.9
|View full text |Cite
|
Sign up to set email alerts
|

New approaches for patients with advanced radioiodine-refractory thyroid cancer

Abstract: The cumulative evidence over the past decades has shown that the incidence of differentiated thyroid carcinoma (DTC) has exponentially increased. Approximately 10% of patients with DTC exhibit recurrent or metastatic disease, and about two-thirds of the latter will be defined as refractory to radioactive iodine (RAIR) treatment. Since this condition implies 10-year survival rates less than 10% after detection, using available treatments, such as systemic and targeted therapies, have become increasingly relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…RAI refractoriness can be defined by different scenarios, such as the absence of RAI uptake at the initial whole body scan (WBS) or in metastatic lesions, or the loss of the capacity to uptake RAI after a previous WBS showing avidly uptake RAI metastases; a progression of the disease in a subject who has previously received RAI, or a cumulative activity of 600 mCi of 131 I; the presence of locally advanced disease that cannot be treated by surgery or evaluated by RAI uptake ( 95 , 96 ). Genetic and epigenetic alterations in the RTK/BRAF/MAPK/ERK and PI3K-AKT-mTOR pathways underly the diminished NIS signalling/activity that lead to RAI refractoriness and to a more aggressive behaviour ( 97 ): their identification can be useful to investigate new compounds able to act against these aberrant molecular mechanisms overcoming the standard cancer therapy resistance.…”
Section: Rai-r Development and Redifferentiation Strategiesmentioning
confidence: 99%
“…RAI refractoriness can be defined by different scenarios, such as the absence of RAI uptake at the initial whole body scan (WBS) or in metastatic lesions, or the loss of the capacity to uptake RAI after a previous WBS showing avidly uptake RAI metastases; a progression of the disease in a subject who has previously received RAI, or a cumulative activity of 600 mCi of 131 I; the presence of locally advanced disease that cannot be treated by surgery or evaluated by RAI uptake ( 95 , 96 ). Genetic and epigenetic alterations in the RTK/BRAF/MAPK/ERK and PI3K-AKT-mTOR pathways underly the diminished NIS signalling/activity that lead to RAI refractoriness and to a more aggressive behaviour ( 97 ): their identification can be useful to investigate new compounds able to act against these aberrant molecular mechanisms overcoming the standard cancer therapy resistance.…”
Section: Rai-r Development and Redifferentiation Strategiesmentioning
confidence: 99%
“…found that the TKI agent significantly increased survival in 12 patients ( 25 ). Recently, the effect of selective kinase inhibitors on diverse DTC targets has been reported ( 26 ). Variable percentages of DTC patients (2–25%) have been reported to have neurotrophic tropomyosin receptor kinase (NTRK) fusions ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pitoia reported a complete response to larotrectinib in a patient with RAI refractory DTC who had a rapid progression on TKI therapy and the disappearance of multiple brain metastases ( 29 ). Additionally, it is known that 5–25% of DTCs contain RET rearrangements ( 26 ). In the open-label, phase 1/2 clinical trial, 20 RET-fusion-positive thyroid cancer patients were included, showing an overall response rate (ORR) of 89% ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study cohort, the median rwPFS was estimated to be 49 months, and more than half of the patients were expected to be alive past 6 years. Previous real-world studies of lenvatinib conducted in the US and other countries reported median PFS ranging from 10 to 35 months, although there could be differences in the patient populations as some of these studies included patients with more than one prior multi-kinase inhibitor treatments [14][15][16].…”
Section: Discussionmentioning
confidence: 99%